Main Ecological Problems of the Aral Sea Region and the Psychology of the Population (Eurasian Scientific Herald, 2023)
The Aral Sea region, once a thriving ecosystem in Central Asia, has been plagued by a multitude of ecological problems over the past few decades. These problems have not only had a devastating impact on the environment but have also affected the psychology of the population living in the region. In this article, we will delve into the main ecological problems of the Aral Sea region and explore the psychological consequences experienced by its inhabitants. In this article, we delve into the main ecological problems of the Aral Sea region and explore the intricate relationship between these challenges and the psychology of the affected population. The Aral Sea crisis is a complex and multifaceted issue that encompasses ecological, social, economic, and psychological dimensions, intertwining the fate of the environment with the mental well-being of those living in its vicinity.